PENGUJIAN TERHADAP JENIS BIOAKTIVATOR PADA PEMBUATAN KOMPOS LIMBAH PERTANIAN - Imam Mahadi; Darmawati Darmawati; Silvy Rachmadani Octavia (UIR Press, 2014)
The aim of this study was to produce compost from rice straw and maize straw in according to SNI 19-7030-2004 and also to know the best bioactivator which can be applicated to those wastes. This study held on February until June 2014. This reasearch used True Experimental Reasearch and Completely Random Used Design (Factorial RAL) from 4 factors and 3 reiterations. The subject was rize straw and maize straw to be composted by using bioactivator EM-4, Acticomp and Orgadec and also cow faeces. This prosedure of reasearch was preparing tools and materials, execution the step of composting, observing the process of composting and finished step. The perception variables are texture, composting time, C/N, temperature, humidity and pH. Data was analyzed in quantitative and qualitative. The result showed that the shrinkage of compost weight was 50%, the texture of compost including to small criteria and showed C/N ratio lower than before. All perception variables showed that compost was according to SNI 19-7030-2004, including temperature, humidity and pH as secondary variables. That result also indicated that EM-4 was the best bioactivator in composting rice straw and maize straw.